2002
DOI: 10.1016/s0038-0717(02)00150-5
|View full text |Cite
|
Sign up to set email alerts
|

Ionic identity of pore water influences pH preference in Collembola

Abstract: A test system described by Van Straalen and Verhoef (1997) was used in order to check whether the endogeic Collembolan Heteromurus nitidus was repelled by acid pH. In each of eight experimental runs sixteen naive animals were allowed to select sectors in a circular pH gradient made of pure quartz sand impregnated with McIlvaine's buffer solutions at constant osmolarity. Disodium or dipotassium hydrogen phosphate was mixed with citric acid in varying proportions, giving rise to acidity levels ranging from pH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Previous work has indicated that even small changes in soil pH, comparable to what we observed in our study, impact Collembola species growth and development, reproduction, fecundity, and longevity (Salmon et al. ). Therefore, N addition enhanced the negative trophic cascade effects of spiders on decomposition by directly reducing Collembola abundance.…”
Section: Discussionsupporting
confidence: 88%
“…Previous work has indicated that even small changes in soil pH, comparable to what we observed in our study, impact Collembola species growth and development, reproduction, fecundity, and longevity (Salmon et al. ). Therefore, N addition enhanced the negative trophic cascade effects of spiders on decomposition by directly reducing Collembola abundance.…”
Section: Discussionsupporting
confidence: 88%
“…An even more important reason was that the set of functional traits used in an ecological study is only a subset of the complete set of traits (including the so-called 'hard traits') needed to assess community responses to environmental change (Lavorel and Garnier, 2002;Garnier et al, 2004). In particular, concerning springtails, we are still in need of physiological traits explaining the response of species to factors such as soil acidity, one of the most complex (although highly influential) ecological determinants of species occurrence (Hågvar, 1990;Loranger et al, 2001;Salmon et al, 2002).…”
Section: Data Collection and Treatmentmentioning
confidence: 99%
“…Pozo (1986) and Cutz-Pool et al (2003) also identified the soil pH as one of the most important factors affecting springtail species distribution, favoring some species and causing the most sensitive ones to disappear. Collembola distribution in acid, neutral or alkaline soils can also be affected by human-induced changes to soil pH, altering their ecological needs (Salmon et al, 2002).…”
Section: Resultsmentioning
confidence: 99%